Thermally enhanced cooperative energy-transfer frequency upconversion in terbium and ytterbium doped tellurite glass - Vermelho, MVD; dos Santos, P. V.; de Araujo, M. T.; Gouveia-Neto, A. S.; Cassanjes, F. C.; Ribeiro, SJL; Messaddeq, Younes [UNESP] (Elsevier B.V., 2003)
Infrared-to-visible frequency upconversion through cooperative energy-transfer and thermal effects in Tb3+/Yb3+-codoped tellurite glasses excited at 1.064 mum is investigated. Bright luminescence emission around 485, 550, 590, 625 and 65 nm, identified as due to the D-5(4) --> F-7(J) (J= 6, 5, 4, 3, and 2) transitions of the terbium ions, respectively, was recorded. The excitation of the D-5(4) emitting level of the Tb3+ ions is assigned to cooperative energy-transfer from pairs of ytterbium ions.. The effect of temperature on the upconversion process was examined and the results revealed a fourfold upconversion enhancement in the 300-500 K interval. The enhancement of the upconversion process is due to the temperature dependence of the Yb3+-sensitizer absorption cross-section under anti-Stokes excitation. A rate-equation. model using multiphonon-assisted absorption for the ytterbium excitation combined with the energy migration effect between Yb-Yb pair, and Tb3+ ground-state depopulation via multiphonon excitation of the F-7(J) excited states describes quite well the experimental results. (C) 2003 Elsevier B.V. B.V. All rights reserved.
Keywords: upconversion; glass; rare earth; temperature